The relationship between types of childbirth, body image, and sexual function in postpartum women - Behnaz Manochehri; Magroom Seniar; Khadija Ahmed; Safiya Sabri Piro; Shiler Ahmadi; Hosna Faridi (Kashan University of Medical Sciences, 2023)
Background: Body image (BI) and sexual functioning can be affected by the rapid and significant physical changes that occur during pregnancy and postpartum.Objectives: This study investigated the relationship between mode of delivery, BI, and sexual function in postpartum women.Methods: This cross-sectional study was conducted between September and November 2021. A total of 203 postpartum women from five health centers in Sanandaj, Iran, were conveniently selected to enroll in this study. Data were collected using an instrument with four sections: demographic data, the Female Sexual Function Index (FSFI), and the Cash and Pruzinsky Multidimensional Body-Self Relations Questionnaire (MBSRQ). Descriptive statistics and binary logistic regression were used to analyze the data.Results: In total, 112 and 91 women had a history of normal vaginal delivery (NVD) or cesarean section (CS), respectively. Compared with the NVD group, women in the CS group had a lower MBSRQ mean (251.95±27.99 vs. 236.75±35.22) and a slightly lower FSFI mean (68.43±9.62 vs. 70.63±11.67). Age of marriage, education (none-academic), occupation (employed), method of contraception (tubectomy), husband's occupation (unemployment), number of children (3-4), FSFI score and MBSRQ score were shown as effective factors on type delivery (P≤0.05).Conclusion: This study showed that women who had a CS were less satisfied with their BI than those who had a NVD. However, the two groups did not differ significantly in terms of their sexual function.